The POTENSI PENGEMBANGAN WISATA AIR BELANTING RIVER TUBING DI DESA WISATA KELUMPANG KABUPATEN OGAN KOMERING ULU - Permatasari, Mustika (Family Welfare Education, 2023)
The musi river hosts one of the water Tours known as the river tour. Musi river tour isa trip that nicmatin tourists use using tourist boats. Certainly musi river touris one of the many tourists able to attract tourists to the city of palembang. According to the researchers' observation that tourist attractions in the musi river have not yet met the components of the good attraction this shows a variety of activities, an inn accommodations are not available and a lack of promotion activities to bring tourists to the musi river. The purpose of this study is to know the potential in the palembang city musi river seen from attractions, amenities and accessibility to can increase the number of tourist visits. Research methods to be used in this study will use qualitative research methods with a case study approach. Using the type of case study, it aims to provide a description of the potential tourist attraction of the musi river. The results and conclusions of this study that the potential of the musi river has given a high opportunity to develop as a tourist attraction. And currently includes the preeminent tourist destination held by the city of palembang. The potential that can support such development as its good cultural and environmental presence can add to the richness of local cultural objects and attractions.